Electrocardiographic characterization of non-selective His-bundle pacing: validation of novel diagnostic criteria - Jastrzębski, Marek; Moskal, Paweł; Curila, Karol; Fijorek, Kamil; Kukla, Piotr; Bednarek, Agnieszka; Kiełbasa, Grzegorz; Bednarski, Adam; Baranchuk, Adrian; Czarnecka, Danuta (Europace, 2019)
AIMS: Permanent His-bundle (HB) pacing is usually accompanied by simultaneous capture of the adjacent right ventricular (RV) myocardium-this is described as a non-selective (ns)-HB pacing. It is of clinical importance to confirm HB capture using standard electrocardiogram (ECG). Our aim was to identify ECG criteria for loss of HB capture during ns-HB pacing. METHODS AND RESULTS: Patients with permanent HB pacing were recruited. Electrocardiograms during ns-HB pacing and loss of HB capture (RV-only capture) were obtained. Electrocardiogram criteria for loss/presence of HB capture were identified. In the validation phase, these criteria and the 'HB ECG algorithm' were tested using a separate, sizable set of ECGs. A total of 353 ECG (226 ns-HB and 128 RV-only) were obtained from 226 patients with permanent HB pacing devices. QRS notch/slur in left ventricular leads and R-wave peak time (RWPT) in lead V6 were identified as the best features for differentiation. The 'HB ECG algorithm' based on these features correctly classified 87.1% of cases with sensitivity and specificity of 93.2% and 83.9%, respectively. The criteria for definitive diagnosis of ns-HB capture (no QRS slur/notch in Leads I, V1, V4-V6, and the V6 RWPT ≤ 100 ms) presented 100% specificity. CONCLUSION: A novel ECG algorithm for the diagnosis of loss of HB capture and criteria for definitive confirmation of HB capture were formulated and validated. The algorithm might be useful during follow-up and the criteria for definitive confirmation of ns-HB capture offer a simple and reliable ancillary procedural endpoint during HB device implantation.
Keywords: Female; Atrioventricular Block; Atrial Fibrillation; ženské pohlaví; Heart Failure; atrioventrikulární blokáda; lidé; srdeční selhání; Sick Sinus Syndrome; Aged, 80 and over; Algorithms; Electrocardiography; elektrokardiografie; Cardiac Pacing, Artificial; Hisův svazek; syndrom chorého sinu; Male; Aged; algoritmy; Bundle of His; fibrilace síní; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; kardiostimulace umělá; Middle Aged; Humans